Psychosocial and biological treatment considerations for the paraphilic and nonparaphilic sex offender - Saleh, FM; Guidry, LL (Journal of the American Academy of Psychiatry and the Law Online, 2003)
There is a growing consensus among clinicians that sex offenders represent a heterogeneous group of individuals. Assessment and treatment of sex offenders is complicated by phenomenological and etiological differences and the presence of psychopathology, including paraphilias. The authors discusses the most commonly employed psychosocial therapies for sex offenders in general. Pharmacologically based treatments for paraphilic sex offenders are also reviewed.